STRATEGIES FOR OVERCOMING SPEECH ERRORS AND ENHANCING FLUENCY IN ENGLISH LANGUAGE LEARNING (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article explores the identification and correction of speech errors among English language learners, focusing on strategies to enhance both oral fluency and linguistic accuracy. The primary purpose of this research is to determine the most effective pedagogical methods for improving students' communicative competence in English. By employing various pedagogical approaches and observational methods, the study concludes that systematic error analysis and targeted practice significantly enhance students' communicative competence. Preventing speech errors not only improves fluency but also increases the overall effectiveness of the language-learning process. The findings underscore the importance of integrating interactive learning, contextual practice, and robust feedback mechanisms to foster an environment conducive to effective language acquisition. This comprehensive approach aims to equip learners with the necessary tools to navigate the complexities of English communication confidently.